The Development of E-Book Based on A Scientific Approach to Train Critical Thinking Ability on The Structure and Function of Plant Tissue Topic - Wulida Mamluatul Faza; Yuni Sri Rahayu (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Educational demands that must be met in the 21st century are mastery of 4C skills (Critical Thinking, Collaborative, Creativity, and Communicative) and centered on higher-order thinking skills (HOTS). One of the HOTS is the ability to think critically. These critical thinking skills can be realized by applying the right learning approach with the support of appropriate learning media, including through a scientific approach. The goal of this research is to create an e-book based on a scientific approach to train critical thinking skills on the structure and function of plant tissues that are valid, practical, and effective. This study used a 4D development model, which included define, design, develop, and disseminate. The methods used to collect data are questionnaires, readability, pretest and posttest, and observation. Data analysis was performed using a quantitative descriptive technique. The e-book's validity was obtained by the assessment of three validators, resulting in a percentage of 97.50% in the very valid category. The practicality of the e-book was obtained by the results of student responses resulting in a percentage of 94.80% in the very practical category, and the readability test using a fry chart was at level 11. The effectiveness of the e-book was obtained by the results of the students' pretest and posttest gain scores resulting in an average of 0.72 in the high category, and the results of observations obtained a score of 3.80 in the very good category. Therefore, the developed e-book is declared valid, practical, and effective for use in learning. Keywords: e-book, scientific approach, structure and function of plant tissues, critical thinking skills.